Inter-Regional Wage Differentials in Portugal: An Analysis Across the Wage Distribution - Pereira, João (2013)
Typically, studies on regional wage differentials are based on ordinary least squares (OLS) estimates. Quantile regression is an alternative approach which allows these differences to be studied across the whole wage distribution. In this study, the quantile regression framework is considered for the analysis of regional wage differences in Portugal. The findings reveal significant differences in wage equations coefficients between regions for the various quantiles. Furthermore, it is concluded that the regional wage differentials and the components explained by differences in endowments and differences in returns increase across the whole wage distribution.